A randomized clinical trial to evaluate the stain removal efficacy of a sodium phytate dentifrice formulation. Issue 2 (7th February 2018) - Milleman, Kimberly R.; Creeth, Jonathan E.; Burnett, Gary R.; Milleman, Jeffery L.
Abstract: Objectives: Phytate is an organic, cyclic polyphosphate analogous to linear condensed polyphosphates used as stain removal agents. This study investigated stain removal efficacy of an experimental sodium phytate‐containing dentifrice compared to a reference dentifrice. Methods: An experimental, moderate abrasivity (relative dentine abrasivity [RDA] ∼130) antisensitivity fluoride dentifrice containing sodium phytate (0.85% w/w as the hexasodium salt) ( n = 111) was compared to a reference, marketed, low‐abrasivity (RDA ∼ 43), anti‐sensitivity fluoride dentifrice ( n = 113), both containing 1150 ppm fluoride as sodium fluoride. Primary efficacy variables were between‐treatment differences in extrinsic dental stain of anterior teeth after 6 and 12 weeks' twice‐daily use, using Lobene stain index (MacPherson modification, MLSI) mean area ( A ) and intensity ( I ) scores. Comparisons included whole‐tooth and hard‐to‐reach areas (gingival, interproximal, body of lingual). Results: At both 6‐ and 12‐week timepoints, MLSI ( A × I ) scores for total area and hard‐to‐reach areas for the experimental dentifrice were statistically significantly lower than baseline ( P < .0001 for all). This was demonstrated for the reference dentifrice at 6 weeks only, for total, interproximal ( P < .0001 for both), and body of lingual ( P = .0395) scores. Compared with the reference, the experimental dentifrice had statistically significantly lower MLSI scores at both 6 and 12 weeks for all outcome variables including both total MLSI ( A × I ) and hard‐to reach areas ( P < .0001 in all cases). Products were generally well‐tolerated. Conclusions: Differences between treatments were considered clinically differentiable. Sodium phytate may therefore be a suitable additive ingredient to improve tooth stain control performance within an otherwise conventional dentifrice formulation. Clinical Significance: Following 6 and 12 weeks brushing, clinically differentiable differences were shown in stain index scores with an experimental dentifrice containing sodium phytate compared to a reference dentifrice without sodium phytate. Sodium phytate may therefore be a suitable additive ingredient to improve tooth stain control performance within an otherwise conventional dentifrice formulation.